Contextualization of the Concept of Nusyūz in Indonesian Marriage Law: Critical Discourse Analysis - Asmaul Husna; Mustaming; Beddu, Rahmawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This research examines the contextualization of the concept of nusyūz in marriage law in Indonesia and the implications for its resolution regarding the act of beating through a discourse analysis approach. The main focus of the research is to analyze how the interpretation and application of the concept of nusyūz originating from Islamic law is adapted in the context of modern Indonesian marriage law, especially regarding the "beating" solution mentioned in classical texts. Using critical discourse analysis methods, this research explores how discourse about nusyūz is formed and interpreted in various legal texts, fiqh literature, and judicial practices in Indonesia. The research results show a shift in the interpretation of the nusyūz concept from a textual to a contextual understanding that is more in line with the principles of gender equality and human rights. Research finds that "beating" solutions need to be recontextualized with more constructive approaches such as mediation and marriage counseling. These findings contribute to the development of Indonesian marriage laws that are more gender